2023
DOI: 10.3390/ijms24076470
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Peptides as a Bridge between Atrial Fibrillation, Heart Failure, and Amyloidosis of the Atria

Abstract: ANP is mainly synthesized by the atria, and upon excretion, it serves two primary purposes: vasodilation and increasing the renal excretion of sodium and water. The understanding of ANP’s role in cardiac systems has improved considerably in recent decades. This review focuses on several studies demonstrating the importance of analyzing the regulations between the endocrine and mechanical function of the heart and emphasizes the effect of ANP, as the primary hormone of the atria, on atrial fibrillation (AF) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Natriuretic peptides are reliable quantitative biomarkers used to assess cardiac stress and are valuable in the diagnosis and management of HF (17,18). In HF patients, these peptides are released either from the ventricles (BNP and NT-proBNP) or the atrium (ANP) in response to increased pressure on the respective cardiac chambers (18,19). While COVID-19 is a relatively new infection and limited research has explored its impact on heart conditions, various mechanisms have been suggested to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Natriuretic peptides are reliable quantitative biomarkers used to assess cardiac stress and are valuable in the diagnosis and management of HF (17,18). In HF patients, these peptides are released either from the ventricles (BNP and NT-proBNP) or the atrium (ANP) in response to increased pressure on the respective cardiac chambers (18,19). While COVID-19 is a relatively new infection and limited research has explored its impact on heart conditions, various mechanisms have been suggested to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…The MOSES trial uses MR-proANP for patient selection, a biomarker that is specifically released by the atrium, implicated in the pathophysiology of AF development, and associated with AF and major adverse cardiovascular events after stroke. [37][38][39] Furthermore, the biomarker cutoff has been validated in several previous stroke populations to be highly associated with AF diagnosed after stroke using Holter ECG (i.e., probably high burden of AF) as well as with major adverse cardiovascular events within 1 year after stroke. [14][15][16]40 The design of the study differs from ARCADIA and ATTICUS further by the fact that the selection is not restricted to the ESUS population because an underlying high-risk cardiac source might also be present in patients with strokes of other etiologies, such as large artery atherosclerosis or small vessel disease (Figure 1).…”
Section: Implications Of the Esus Definition On Af Screening Poststrokementioning
confidence: 99%
“…ANP causes a reduction in expanded extracellular fluid volume by increasing renal sodium excretion. The authors review the diagnostic and therapeutic relevance of ANP in cardiovascular disease, especially atrial fibrillation and heart failure and discuss possible repercussions of cardioversion procedures and cardiac chirurgical interventions on ANP levels [18]. In his review for this Special Issue, Ivan Melnikov and co-authors analyze the knowledge about the impact of the NLRP3 inflammasome, especially the different C-reactive protein (CRP) isoforms, on atherosclerotic cardiovascular disease.…”
mentioning
confidence: 99%